Starting a cultural collective for mothers of children with disabilities: A case study - Solfrid Raknes; Siv Elin N. Sæbjørnsen; Hege C. Aarlie; Thrine Marie N. Bromstad; Mariana J. Makuu; Caroline Yamala; Sarah Hean (African Journal of Disability)
Background: Caring for children with disabilities in Tanzania involves significant challenges, including stigma, limited support and mental health risks. A cultural collective for caretakers of children with disabilities enrolled at a primary school was established to address these issues.